Chapter I gesuati a Chiusi - Mignoni, Giovanni (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The presence of the Gesuati in Chiusi, although limited in size and length of time, developed beyond all expectation. At the beginning of the seventeenth century the followers of the Blessed Colombini were called to officiate at the church of the "Madonna della Quercia al Pino" in the countryside just outside Chiusi. The friars arrived at a difficult moment after other religious orders had relinquished the post. The Gesuati did their utmost for the spiritual good of the faithful as well as the material good of the church. Unfortunately after only a few years, the Bishop of Chiusi entrusted the building to a secular priest effectively closing the little convent. The conflict which followed between the church, the diocese and the municipality only worsened the situation to the deep regret of the faithful.